2019
DOI: 10.3390/antiox8080267
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotection of Mentha aquatica L., Lavandula dentata L. and Leonurus cardiaca L.

Abstract: The phenolic composition of hydroethanolic extracts of Mentha aquatica L., Lavandula dentata L. and Leonurus cardiaca L., obtained from plants grown under organic cultivation, was determined and their hepatoprotective effects were investigated in vitro. L. cardiaca extract was rich in phenylethenoid glycosides, especially lavandolifolioside (254 ± 36 μg/mg), whereas rosmarinic acid and eriodictyol-O-rutinoside were the major phenolic compounds of L. dentata and M. aquatica extracts, accounting for 68 ± 7 μg/mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 41 publications
2
5
0
Order By: Relevance
“…In the case of DPPH, the n-hexane, ethyl acetate, and dichloromethane extract did not show radical scavenging action, and there was a positive relation with the HPLC-online-DPPH of these extracts. Methanol extract exhibited a notably reduced DPPH scavenging activity, in agreement with the studies of Pereira et al, which found an EC50 value of 18.3 μg/mL in the DPPH test performed on L. cardiaca hydroethanolic extracts [37]. Furthermore, a study carried out by Jafari et al revealed that the hydroalcoholic extract of L. car-diaca had higher antioxidant activity (IC50 53.79 μg/mL) than ethyl acetate extract (IC50 107.16 ug/mL) [38].…”
Section: In Vitro Antioxidant Activitysupporting
confidence: 91%
See 1 more Smart Citation
“…In the case of DPPH, the n-hexane, ethyl acetate, and dichloromethane extract did not show radical scavenging action, and there was a positive relation with the HPLC-online-DPPH of these extracts. Methanol extract exhibited a notably reduced DPPH scavenging activity, in agreement with the studies of Pereira et al, which found an EC50 value of 18.3 μg/mL in the DPPH test performed on L. cardiaca hydroethanolic extracts [37]. Furthermore, a study carried out by Jafari et al revealed that the hydroalcoholic extract of L. car-diaca had higher antioxidant activity (IC50 53.79 μg/mL) than ethyl acetate extract (IC50 107.16 ug/mL) [38].…”
Section: In Vitro Antioxidant Activitysupporting
confidence: 91%
“…Free radicals are accountable for oxidative damage to vital biomolecules. Keeping an equilibrium between oxidants and free radicals is a prerequisite for good health [8,37].…”
Section: In Vitro Antioxidant Activitymentioning
confidence: 99%
“…Palavras-chave: Lavandula dentata, cultivo in vitro, óleos essenciais, multiplicação massal. demonstrated (Pereira et al, 2019). Martins et al (2019) identified more than 20 compounds in the essential oil of this species, which confirms its potential for the industry.…”
Section: Researchsupporting
confidence: 62%
“…To this end, the chemical compositions of tested L. cardiaca extracts were determined by HPLC-DAD-MS analysis. Data regarding L. cardiaca total bioactive compounds levels have been addressed in earlier studies [6,[26][27][28][29]. Different levels were observed in these studies.…”
Section: Total Phenolic and Flavonoid Contentmentioning
confidence: 99%